2004
DOI: 10.1136/ard.2003.006296
|View full text |Cite
|
Sign up to set email alerts
|

Development of the PsAQoL: a quality of life instrument specific to psoriatic arthritis

Abstract: Background: Patient reported outcome measures used in studies of psoriatic arthritis (PsA) have been found to be inadequate for determining the impact of the disease from the patient's perspective. Objective: To produce the PsAQoL, a PsA-specific quality of life (QoL) instrument, employing the needs based model of QoL that would be relevant and acceptable to respondents, valid, and reliable. Methods: Content was derived from qualitative interviews conducted with patients with PsA. Face and content validity wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
149
0
20

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(176 citation statements)
references
References 15 publications
7
149
0
20
Order By: Relevance
“…Pain may interfere with the activities related to daily life and thus cause poor functional status and diminished QoL. Similar to our study, McKenna et al 13 and Billing et al 19 reported a significant correlation between subgroups of NHP and PsQoL scores. Thus, we can consider the Turkish version of VITACORA-19 as a questionnaire that evaluates the QoL of PsA patients multi-dimensionally.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Pain may interfere with the activities related to daily life and thus cause poor functional status and diminished QoL. Similar to our study, McKenna et al 13 and Billing et al 19 reported a significant correlation between subgroups of NHP and PsQoL scores. Thus, we can consider the Turkish version of VITACORA-19 as a questionnaire that evaluates the QoL of PsA patients multi-dimensionally.…”
Section: Discussionsupporting
confidence: 90%
“…As in our study, they also showed no effect of the presence of psoriasis treatment on PsQoL. 13 In the study by Wink et al, 18 the male patients had higher PsQoL scores, as in our study. Similar to the previous studies, patients who do not perceived current severity of arthritis as mild or those who had no flare of arthritis had higher VITACORA-19 score indicating that presence and severity of arthritis are among the main parameters determining the level of HRQoL.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Patients filled in the validated Hungarian version of the Health Assessment Questionnaire (HAQ), EQ-5D and Psoriatic Arthritis Quality of Life Questionnaire (PsAQoL) [5][6][7][8].…”
Section: Assessmentmentioning
confidence: 99%